The hungry mind : the origins of curiosity in childhood - Engel, Susan L., 1959- (Harvard University Press, 2015)
"A deeply researched ... exploration of what curiosity is, how it can be measured, how it develops in childhood, and how it can be fostered in school."--Jacket